Genetic structure and phenotypic differences among and within extant populations of Chrysanthemum arcticum L. and C. a. subsp. arcticum - Liu, Yunjia (2020)
University of Minnesota M.S. thesis. July 2020. Major: Conservation Biology. Advisor: Neil Anderson. 1 computer file (PDF); viii, 144 pages. Chrysanthemum arcticum L., Arctic daisy, (=Arctanthemum arcticum; =Dendranthema arcticum) and its two subspecies (C. arcticum L. subsp. arcticum, C. arcticum L. subsp. polaré Hulten), collectively the C. arcticum species complex, are the only chrysanthemum species native to North America. The species are of interest since they are salt tolerant, growing only along the oceans, with a groundcover habit and may possess other ornamental traits of value to chrysanthemum breeders. However, evidence of decline in species’ range of distribution were detected, which may be reducing the genetic diversity. Understanding the genetic diversity and population structure is important in order to develop conservation strategies and utilize valuable germplasm resources. Thus, we have collected and genotyped 529 genotypes in nine C. arcticum and 21 C. a. ssp. arcticum extant populations from the State of Alaska mainland and Attu Island (the westernmost Aleutian Island). Population genetic diversity was analyzed using 7,449 SNP markers from DArTseqLD. Simultaneously, 16 quantitative morphological traits and 5 qualitative morphological traits were investigated for phenotypic differences. Three distinct genetic clusters were detected by STRUCTURE 2.3.4 within C. arcticum populations and consistent results were obtained with Principal coordinate analysis (PCoA), Discriminant analysis of principal components (DAPC), and the Unweighted pair group method with arithmetic means (UPGMA), while a mixture of subgroups were present in C. a. subsp. arcticum populations genetic cluster analyses, which may be the result of gene flow among close populations capable of gene exchange (Chapter 2). The study on the species’ variation in morphological and diagnostic traits is of importance to enhance diagnostic traits for species identification and link morphological traits with single nucleotide polymorphism (SNP) markers. Soil samples revealed extremely high levels of Na, which confirmed that the species are salt-tolerant. Univariate ANOVAs revealed significant differences among species and morphological traits, similar to the genetic structure analysis for variation among populations within members of the C. arcticum species complex. Overlaps in the genetic cluster analysis for C. a. subsp. arcticum verified the possibility of a higher frequency of gene flow among Attu island collection sites (chapter 3).